2009
DOI: 10.1002/bmc.1311
|View full text |Cite
|
Sign up to set email alerts
|

Quality assessment of Cortex Phellodendri by high‐performance liquid chromatography coupled with electrospray ionization mass spectrometry

Abstract: A simple method based on liquid chromatography coupled with diode array detection and electrospray ionization mass spectrometry (LC-DAD-ESI-MS) was developed for the quality assessment of Cortex Phellodendri (CP), which was mainly derived from two species of Phellodendron chinense Schneid and Phellodendron amurense Rupr. Total 41 compounds, including 14 phenols, 24 alkaloids and three liminoidal triterpenes were identified or tentatively characterized from the 75% methanol extract of CP samples by online ESI-M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
45
0
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 51 publications
(49 citation statements)
references
References 21 publications
3
45
0
1
Order By: Relevance
“…The extract of this herb suppresses the synthesis of collagen and promoted the synthesis of proteoglycans in chondrocytes (33). Alkaloids are the principal active components of the bark of the Chinese Corktree (33).…”
Section: Discussionmentioning
confidence: 99%
“…The extract of this herb suppresses the synthesis of collagen and promoted the synthesis of proteoglycans in chondrocytes (33). Alkaloids are the principal active components of the bark of the Chinese Corktree (33).…”
Section: Discussionmentioning
confidence: 99%
“…. Combined with their chromatography behavior analysis, lotusine and oblongine were excluded because of faster elution than magnolflorine (Hu et al, 2010). However, magnocurarine was eluted slower than magnolflorine by comparison with standard (Nikolić et al, 2012).…”
Section: Analysis Of Prototype Compoundsmentioning
confidence: 98%
“…Peaks 7 and 8 are the other types of alkaloids. As the reference chemicals unavailable, they were tentatively identified by retention behaviors, MS and MS/MS spectra with those of literature data (Liang et al, 2006;Hu et al, 2009). All the flavonoids detected in the experiment (peaks 9, 10, 16, 17, 18, 19, 20 and 22) (Han et al, 2007), it was tentatively identified as oroxylin A-7-O-glucuronide.…”
Section: Screening Of the Prototype Components In Rat Plasmamentioning
confidence: 99%